2013
DOI: 10.1149/2.011306jes
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Chromium by Square-Wave Adsorptive Cathodic Stripping Voltammetry at an Improved Bismuth Film Electrode

Abstract: A square-wave adsorptive cathodic stripping voltammetric protocol coupled with an improved bismuth film electrode (BiFE) for the determination of trace chromium in the presence of 4-(2-pyridylazo) redorcinol (PAR) has been investigated. A well-defined and sensitive stripping peak of the Cr(III)-PAR complex was observed at −0.57 V (versus SCE) in a 0.1 mol/L acetate buffer solution (pH 5.0) at a deposition potential of −0.45 V. The experimental variables as well as potential interferences were studied. Compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…In the recent years, the SW voltammetry has emerged as a viable and cheap alternative to the expensive and time-consuming techniques (such as chromatography, or spectrophotometry, for example) for the determination of inorganic and biologically important compounds. The simple working set-up, the quick time of performing the measurements, the different modes that can be applied, together with its sensitivity, make the SWV a technique of choice for quantification of important classes of compounds such as proteins [82], vitamins [83], phenols [84][85][86][87][88], benzoquinones [89], pesticides, herbicides and fungicides [90][91][92][93][94][95][96][97][98], alkaloids [99], terpenoids [100], heavy metals [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116], and drugs [117,118]. One of the most valuable ability of SWV is its application for simultaneous determination of compounds with similar structures present in various pharmaceutical and physiological samples.…”
Section: Analytical and Biochemical Applications Of Square-wave Voltamentioning
confidence: 99%
“…In the recent years, the SW voltammetry has emerged as a viable and cheap alternative to the expensive and time-consuming techniques (such as chromatography, or spectrophotometry, for example) for the determination of inorganic and biologically important compounds. The simple working set-up, the quick time of performing the measurements, the different modes that can be applied, together with its sensitivity, make the SWV a technique of choice for quantification of important classes of compounds such as proteins [82], vitamins [83], phenols [84][85][86][87][88], benzoquinones [89], pesticides, herbicides and fungicides [90][91][92][93][94][95][96][97][98], alkaloids [99], terpenoids [100], heavy metals [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116], and drugs [117,118]. One of the most valuable ability of SWV is its application for simultaneous determination of compounds with similar structures present in various pharmaceutical and physiological samples.…”
Section: Analytical and Biochemical Applications Of Square-wave Voltamentioning
confidence: 99%
“…Determination of total Cr was carried out according to a modification of our previous work [34] by replacing a bismuth film electrode with the Au-PET electrode.…”
Section: Determination Of Total Chromiummentioning
confidence: 99%
“…And it was obvious that the BiFE (d) electrodeposited in HAc-NaAc medium containing sodium citrate also showed a better electroanalytical performance for determination of Ge(IV) than the BiFE (c). According to Zhang et al [25] and Nunes and Faria [26], the significant improvement was due to the addition of trisodium citrate that helped form a homogeneous structure by aggregates of spherical particles with a few nanometers in diameter. We also investigated the effect of KBrO 3 on the electrochemical behavior of germanium(IV)-pyrogallol complex at the improved bismuth film electrode.…”
Section: Electrochemical Behavior Of Germanium(iv)-pyrogallolmentioning
confidence: 99%
“…However, there is no report about the determination of germanium in Chinese herbal remedies by using BiFEs so far. And our group found that the analytical performance of bismuth film electrode was significantly improved by adding citrate to a relatively higher pH electrodeposition solution [25].…”
Section: Introductionmentioning
confidence: 98%